Answer:
23x = -115
Step-by-step explanation:
In the substitution method, you must solve for 1 variable in 1 equation to replace it in the other equation. For the system:
2x - 7y = 4
3x + y = -17
Solving for y in the second equation:
y = -17 - 3x
Replacing y in the first equation:
2x - 7(-17 - 3x) = 4
2x + 119 + 21x = 4
23x = -115
This is the new equation after use the substitution method.
The answer is 72
You would have to add sixty-five plus seven
Answer:
I do not see a image
Step-by-step explanation:
We'll have to assume that interest is charged annually.
interest = i = p*r*t, where p is the initial amount ($25000), r is the annual interest rate as a decimal fraction, and t is the length of time, in years.
Then $2625 = $25000*0.035*t. Solve for t:
$2625
------------ = 0.035t = 0.105. Dividing both sides by 0.035, we get
$25000
t = 3 years (answer)
Answer:
y - 6 = -4(x+1) is equivalent to equation C: y = -4x + 2
Step-by-step explanation:
Solve the given y - 6 = -4(x+1) for y and remove the parentheses shown:
y - 6 = -4(x+1) becomes
y = -4(x + 1) + 6, or
y = -4x - 4 + 6, or
y = -4x + 2 This is equivalent to equation C.